FEATURES OF THE DETERMINATION OF ECONOMIC CRIME IN MODERN CONDITIONS (Bulletin of criminological association of Ukraine, 2023)
In the article, based on the analysis of scientific views of scientists, the author's definition of the concept of "economic crime" is proposed. The causes and conditions that determine the occurrence of economic crime in Ukraine are singled out. It was established that economic crime is a socially dangerous phenomenon that affects not only the economic and financial state of the state and society, but also the social and political development of the country as a whole.
Keywords: crime; causes; conditions; economic crime; criminal law